Pengaruh Latihan Beban Terhadap Peningkatan Kerampilan Tendangan Sabit Pada Atlet Perguruan Pencak Silat Persinas Asad Kota Palopo - Julian Sigap Rosadi Suwarso; Hidayat, Rachmat; Riswanto, A. Heri (Jurnal Porkes, 2025)
The low quality of crescent kick skills, which includes aspects of speed, accuracy, strength, balance, and coordination. This is often caused by a lack of leg muscle strength and body stability, which are vital physical components to support the effectiveness of kicking techniques. This study aims to empirically test the effect of weight training on improving the skill of the sabit kick in Pencak Silat athletes from the Persinas ASAD Academy in Palopo City. The method used is a quasi-experiment with a one-group pretest-posttest design. The sample consisted of 10 athletes selected through purposive sampling. The intervention consisted of a leg muscle weight training program (such as squats, lunges, calf raises, and leg presses). Data were collected using a validated observation sheet and analyzed using a paired sample t-test. The results of the study proved a significant increase, where the average score for scythe kick skills rose from 65.30 (fair category) in the pretest to 79.60 (good category) in the posttest. The t-test results showed a significance value of 0.000 (p < 0.05). The conclusion of this study is that weight training has a significant and positive effect on improving the skill of the sabit kick.